(untitled) (Revista Venezolana de Salud Pública, 2018)
A descriptive transversal investigation was conducted with the aim of evaluating the exposure to psycho-social risks in a stratified sample of 556 workers of the main areas of economic activities in Lara State, Venezuela. The questionnaire for evaluation of psychosocial risk in the workplace (ISTAS) was applied for the identification and measurement of exposure of workers to psychosocial demands related to claims about labor and control over job content. The results indicate that the proportion of workers exposed to situations most unfavourable to health is low (9% to 27%) prevailing dimensions of double presence and psychological demands. The rate exposure for intermediate situations is relatively high (55% to 69%) in the psychological demands dimension, active work, skill development and also compensation. Workers with higher exposures are those belonging to financial, insurance and real estate industries, shops, restaurants and hotels. The results from this study suggest that the workers whose activity involves customer interactions are exposed to higher psychological (cognitive and emotional) demands and they are limited to make decisions about their tasks, have almost no chance of skill development or control over their working time. Workers under community, social and personal service activities perceive that compensations received (stability and esteem) are not in accordance with their efforts. Social support and leadership was the dimension perceived as the most favorable for the health of all workers.